TXNIP hypomethylation and its interaction with obesity and hypertriglyceridemia increase type 2 diabetes mellitus risk: A nested case‐control study. Issue 7 (23rd January 2020) - Zhang, Dongdong; Cheng, Cheng; Cao, Meng; Wang, Tieqiang; Chen, Xiaoliang; Zhao, Yang; Wang, Bingyuan; Ren, Yongcheng; Liu, Dechen; Liu, Leilei; Chen, Xu; Liu, Feiyan; et al.
Abstract: Background: This study aims to estimate type 2 diabetes mellitus (T2DM) incidence with DNA methylation of the thioredoxin‐interacting protein ( TXNIP ) gene and its interaction with environmental factors. Materials and Methods: This case‐control study included 286 incident T2DM cases and 286 non‐T2DM controls matched by sex, age, marital status, race, and residence village nested in the Rural Chinese Cohort Study. A conditional logistic regression model was used to estimate the association of DNA methylation at TXNIP gene with T2DM risk. Also, multifactor dimensionality reduction (MDR) and classification and regression tree (CART) analyses were used to investigate the interaction between TXNIP methylation and environmental risk factors. Results: Methylation levels of all five CpG loci at TXNIP gene were significantly lower in T2DM than in controls (all P < .001). With increasing methylation level, risk of T2DM was significantly decreased (odds ratio, 95% CI 0.80, 0.69‐0.94 for CpG1; 0.80, 0.69‐0.93 for CpG2; 0.70, 0.56‐0.88 for CpG3; 0.78, 0.66‐0.92 for CpG4; and 0.76, 0.60‐0.97 for CpG5). Additionally, the essential interactions among TXNIP methylation, obesity, and hypertriglyceridemia were identified by CART and MDR analyses. On logistic regression analysis, the risk of T2DM was reduced with terminal node 5 (CpG3 methylation ≥72%, nonobesity, normal triglyceride (TG) level, and CpG4 methylation ≥83%) vs terminal node 1 (CpG3 methylation <72%) (odds ratio 95% CI 0.20, 0.10‐0.40). Conclusions: TXNIP methylation is associated with T2DM incidence in a Chinese population. Interaction between TXNIP methylation and environmental factors may influence T2DM risk and needs more investigation. Abstract : Highlights This is the first prospective nested case‐control study in rural Chinese people to estimate the association of the methylation level of the thioredoxin‐interacting protein ( TXNIP ) gene and its interaction with type 2 diabetes mellitus (T2DM) risk. We found a significant negative association between the methylation level of TXNIP gene and T2DM incidence. Interaction among TXNIP gene hypomethylation, obesity, and hypertriglyceridemia increased the risk of T2DM. 摘要: 背景: 本研究旨在分析 TXNIP 基因甲基化及其与环境因素的交互作用与2型糖尿病(type 2 diabetes mellitus, T2DM)发病风险之间的关联。 方法: 本研究采用病例对照研究设计, 在中国农村队列研究中按照年龄、性别、婚姻状况、种族和居住地五等条件进行1:1匹配, 纳入病例、对照各286人。采用条件logistic回归模型, 分析 TXNIP 基因甲基化与T2DM之间的关联; 采用多因素降维法(multifactor dimensionality reduction, MDR)和分类回归树(classification and regression tree, CART)评价 TXNIP 甲基化与环境风险因素之间的交互作用。 结果: T2DM组 TXNIP 基因的5个CpG位点甲基化水平均显著低于对照组(P<0.001)。随着甲基化水平的增加, T2DM风险显著降低(OR [95%CI]:CpG1, 0.80 [0.69‐0.94]; CpG2, 0.80 [0.69‐0.93]; CpG3, 0.70 [0.56‐0.88]; CpG4, 0.78 [0.66‐0.92]; CpG5, 0.76 [0.60‐0.97])。此外, CART和MDR结果显示, TXNIP 甲基化、肥胖和高甘油三酯血症之间存在交互作用。Logistic回归分析显示, 与终末节点1亚组人群(CpG3甲基化<72%)相比, 终末节点5亚组人群(CpG3甲基化≥72%、非肥胖、甘油三酯(TG)水平正常, 且CpG4甲基化≥83%)发生T2DM的风险较低(OR=0.20, 95%CI:0.10 0.40)。 结论: 在中国人群中, TXNIP 基因甲基化水平与T2DM的发生风险有关。 TXNIP 甲基化与环境因素的交互作用可能影响T2DM风险, 但还需要进一步研究。